The Effects of Surgery on Leukocyte Vitamin C Concentrations: A Systematic Review and Meta-Analysis - Nikolaj Travica; Karin Ried; Irene Hudson; Andrew Scholey; Andrew Pipingas; Avni Sali (Tabriz University of Medical Sciences, 2022)
Background: Vitamin C (ascorbic acid) is a micronutrient imperative for many bodily functions, with research revealing its functional support of leukocytes. The purpose of this meta-analysis was to determine the effects of surgery on leukocyte vitamin C concentrations by assessing the amount and longevity of post-operative leukocyte vitamin C change. Methods: We searched the PubMed, Scopus and the Cochrane Library databases for relevant research papers. Studies were included until January 2022, with no time limits. Studies that reported means and standard deviations of leukocyte/buffer layer vitamin C concentrations before and after surgery were included into the meta-analysis. The meta-analysis comprised of eight studies. Results: Seven studies (which included eight individual studies) were included into our meta-analysis. Combined data from the meta-analysis displayed a significant depletion in mean leukocyte vitamin C concentrations during the first 24 hours following the surgery by a mean of 5.37 µg/108 (32.3%) (CI = -6.35, -4.40) (n = 6, p < 0.001) and during the first post-operative week by 4.43 µg/108 (23%) (-7.27, -1.58) (n = 7, p < 0.001). However, this depletion was followed by an uprise in mean ascorbic acid leukocyte concentrations of 0.93 µg/108 (4.8%) (-0.79, 2.66) (n = 6, p = 0.29) at 7 days (or beyond) post-operatively. Conclusion: Significant post-operative leukocyte vitamin C depletions were particularly observed during the first post-operative week. Further research is required to validate the observed results and to determine whether the observed depletions may be linked to compromised immunological function and pathophysiologies that arise during the post-operative period.